2015
DOI: 10.17139/raab.2015.0017.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Riesgo de anomalías congénitas en grupos étnicos de Sudamérica

Abstract: RESUMEN El objetivo del trabajo fue estimar el riesgo de defectos congénitos según condición étnica de los padres del recién nacido. Fueron seleccionados 20.940 neonatos con 10 anomalías congénitas específicas y un grupo similar de controles, clasificados según su condición étnica. Se estimaron los riesgos de las 10 anomalías congénitas aisladas mediante métodos de regresión logística, ajustando los riesgos por índices de propensión (Propensity Score) utilizando la prueba de Mantel-Haenszel. Los resultados del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(30 reference statements)
0
1
0
1
Order By: Relevance
“…In our sample, PreP newborns with Afro American ancestry had older fathers and a higher risk for PreP than newborns without black ancestry, as well as a greater familial recurrence rate of this defect (data not shown). Considering that the frequency of PreP is low among Afro Americans especially when compared to Native Americans (Bingle & Niswander, 1975;Campaña et al, 2010;Castilla et al, 1973;Villalba et al, 2015), the observed higher recurrence rate among the former would be suggesting a single etiologic factor, and accordingly, in 8/12 of our PreP cases with African ancestry, the pedigrees suggested autosomal dominant inheritance. This mode of inheritance has repeatedly been mentioned for PreP.…”
Section: Discussionmentioning
confidence: 71%
“…In our sample, PreP newborns with Afro American ancestry had older fathers and a higher risk for PreP than newborns without black ancestry, as well as a greater familial recurrence rate of this defect (data not shown). Considering that the frequency of PreP is low among Afro Americans especially when compared to Native Americans (Bingle & Niswander, 1975;Campaña et al, 2010;Castilla et al, 1973;Villalba et al, 2015), the observed higher recurrence rate among the former would be suggesting a single etiologic factor, and accordingly, in 8/12 of our PreP cases with African ancestry, the pedigrees suggested autosomal dominant inheritance. This mode of inheritance has repeatedly been mentioned for PreP.…”
Section: Discussionmentioning
confidence: 71%
“…Sin embargo, hubo diferencias en cuanto al acceso a un tratamiento estándar en el grupo más favorecido en cuanto a sus características sociosanitarias, ya que aquellos niños con ambos padres ocupados, o con un mayor nivel educativo, tuvieron un tratamiento específico con mejores puntajes de integralidad, interdisciplina y oportunidad. Varias investigaciones tanto internacionales (42,44,45) como locales (43,203,204) han postulado que las desventajas sociales y económicas son factores que aumentan el riesgo para concebir un hijo con FLAP, lo que pone a las familias más vulnerables en una doble situación de desigualdad: haber concebido a un hijo con la malformación, y tener el riesgo de recibir un tratamiento menos oportuno, integral o interdisciplinario para afrontarla.…”
Section: Características Sociosanitarias De Las Familiasunclassified